Analisis Kekasaran Baja AISI 304 Akibat Variasi Parameter pada Proses Roughing CNC Turning Menggunakan Pahat Cermet - Nugroho Setyo Pambudi (Universitas Negeri Malang, 2020)
Abstract: This study aims to determine the surface roughness value of AISI 304 steel due to variations in spindle speed and feed motion. The method used is pre-experimental design and data analysis techniques used are descriptive analysis techniques. The spindle rotation speed used is 1990 rpm, 2100 rpm, and 2300 rpm, while the feed motion used is 0.18 mm / rev, 0.23 mm / rev, and 0.28 mm / rev. The cutting tool used in this study is a Mitsubishi brand insert chisel with ISO standard CNMNG120404-MA, while the data collection technique using a measuring tool to measure the surface roughness of the workpiece is the Surface Roughness Test Mitutoyo Portable Surftest SJ 301 series. The results of this study indicate that high engine speed reaches 2300 Rpm and low feed motion reaches 0.18 mm / rev resulting in low surface roughness levels reaching 2.17 µm. While the highest is obtained at low engine speed and high feed motion which reaches 1900 Rpm and 0.28 mm / rev with a surface roughness value of 4.43 µm.Keywords: Spindle rotation, feed speed, turning, CNC lathe, surface roughness.